Development of E-Modules Based on Whatsapp Media on IPA Mapel at SDN Gedangmas 02 Lumajang - Saimah; Rufii; Harwanto (Institute of Computer Science (IOCS), 2022)
The purpose of this development is this development is to produce an E-Module Based on Whatsapp Media. The development model used in the development of interactive learning multimedia is the Borg & Gall model. The development process involves subject matter experts, learning design experts and learning media experts to provide feedback and suggestions for improvement. In addition, the science teacher and class VI students at SDN Gedangmas 02 Lumajang as users of the Whatsapp Media-Based E-Module also gave their feedback and input. The use of Whatsapp Media-Based E-Module Development using the ADDIE model for science subjects can effectively increase active learning interactions. The results of this development research are that this Whatsapp Media-Based E-Module Product has a material feasibility level of 93%, a learning design feasibility 94%, and a learning media feasibility 91%. While the small group trial rate is 91.75% and based on field trials 92.11% with very feasible qualifications and does not need to be revised.